Novel group of tyrosyl-DNA-phosphodiesterase 1 inhibitors based on disaccharide nucleosides as drug prototypes for anti-cancer therapy. (1st January 2018) - Komarova, Anastasia O.; Drenichev, Mikhail S.; Dyrkheeva, Nadezhda S.; Kulikova, Irina V.; Oslovsky, Vladimir E.; Zakharova, Olga D.; Zakharenko, Alexandra L.; Mikhailov, Sergey N.; Lavrik, Olga I.
Abstract: A new class of tyrosyl-DNA phosphodiesterase 1 (TDP1) inhibitors based on disaccharide nucleosides was identified. TDP1 plays an essential role in the resistance of cancer cells to currently used antitumour drugs based on Top1 inhibitors such as topotecan and irinotecan. The most effective inhibitors investigated in this study have IC50 values (half-maximal inhibitory concentration) in 0.4–18.5 µM range and demonstrate relatively low own cytotoxicity along with significant synergistic effect in combination with anti-cancer drug topotecan. Moreover, kinetic parameters of the enzymatic reaction and fluorescence anisotropy were measured using different types of DNA-biosensors to give a sufficient insight into the mechanism of inhibitor's action.